GDP growth and convergence determinants in the European Union: a crisp-set analysis - Paulo Ferreira; Andreia Dionísio (Review of Economic Perspectives, 2016)
Economic growth and convergence remains a topical issue. This study uses a crisp-set qualitative comparative analysis of data from European Union countries in order to establish which conditions could be considered necessary and sufficient to make these countries converge. Based on six different conditions (GDP, secondary education, life expectancy, fertility rate, government consumption and inflation rate), this study finds that the main conditions affecting convergence are government consumption ratio (lower levels will increase convergence), education levels and life expectancy (both with a positive influence on convergence). The first two conditions show quite interesting results: in fact, reduction of government expenditure and budget constraints are an open debate; and the European Union's aim to become a more competitive economy can only be attained with higher levels of education.
Keywords: 330; Convergence; crisp-set qualitative comparative analysis; European Union; necessary conditions; sufficient conditions